Aetiology and Presentation of Intestinal Obstruction among Patients Presenting to a Tertiary Hospital in Uganda - Nakanwagi, Arlene Muzira; Kijjambu, Stephen C.; Ongom, Peter; Luggya, Tonny Stone (Int J Crit Care Emerg Med, 2016)
Intestinal Obstruction is the impairment of normal flow of intestinal contents from mouth to anal canal with aetiology that varies depending on various factors. Understanding aetiology of a country’s surgical services has proven to aid better planning for its emergency surgical conditions. Mulago, which is Uganda’s National Referral Hospital, is resource constrained with a surgical burden of 33% due to acute abdomen with Intestinal Obstruction. This study aimed to determine the current presentation pattern and etiological factors of Intestinal Obstruction at Mulago. Ethical approval was got, from Makerere University School of Medicine IRB, to carry out a prospective observational study among surgical patients admitted to Mulago Hospital’s surgical wards and units. All patients admitted to the hospital for the study period that fitted the inclusion criteria, with suspected partial or complete Intestinal Obstruction or those with confirmed diagnosis intraoperatively were consented and enrolled. Results: We recruited 110 with 79 (71.8%) males and 31 (28.2%) females. Paediatric patients of 0-12 years were 45 (41.0%) and 65 (59%) were adults above 13 years. We had 50% that presented after 72 hrs of symptoms, 24.6% of these were initially managed in a health centre and only 7.3% of the participants presented within 24 hours. The commonest symptoms that presented were colicky abdominal pain, vomiting, abdominal distension and relative constipation. Hernias were the commonest cause of Intestinal Obstruction in adults followed by gut volvulus then adhesions and tumours while in the paediatric group had intussusceptions as the most common aetiological factor followed by Anorectal malformations and then congenital atresia plus stenosis as third commonest cause of in children respectively. Hernias followed by intestinal volvulus were the commonest adult aetiology while intussusceptions followed by Anal Rectal Malformations were the commonest paediatric aetiology of intestinal obstruction. In Mulago hospital with colicky abdominal pain, abdominal distension and vomiting as the commonest presenting symptoms with males the predominantly affected sex.